2015
DOI: 10.1158/2326-6066.cir-14-0117
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Mouse Pluripotent Stem Cell–Derived Proliferating Myeloid Cells as an Unlimited Source of Functional Antigen-Presenting Cells

Abstract: The use of dendritic cells (DC) to prime tumor-associated antigen-specific T-cell responses provides a promising approach to cancer immunotherapy. Embryonic stem cells (ESC) and induced pluripotent stem cells (iPSC) can differentiate into functional DCs, thus providing an unlimited source of DCs. However, the previously established methods of generating practical volumes of DCs from pluripotent stem cells (PSC) require a large number of PSCs at the start of the differentiation culture. In this study, we genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…Therefore, ex vivo DC manufacturing has an immediate biotechnological application. DC generation from PSCs is a promising approach; however, PSC-derived DCs often exhibited a suboptimal T cell-activation capacity (6,11,13). Consistent with this notion, in this study we found that ES cell-derived DCs represented less mature cells compared with adult stem cell-derived DCs.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, ex vivo DC manufacturing has an immediate biotechnological application. DC generation from PSCs is a promising approach; however, PSC-derived DCs often exhibited a suboptimal T cell-activation capacity (6,11,13). Consistent with this notion, in this study we found that ES cell-derived DCs represented less mature cells compared with adult stem cell-derived DCs.…”
supporting
confidence: 86%
“…In this study, we examined the transcription factor network in stem cell-derived differentiated immune cells. GM-CSF-dependent dendritic cell (DC) development was selected as a differentiation model because this cell type can be generated from adult stem cells and ES cells (6)(7)(8)(9)(10)(11)(12)(13). Moreover, numerous transcription factors were described that control the commitment and specification of DCs (14,15).…”
mentioning
confidence: 99%
“…21 Measurement of cytokines Cytokine levels in culture supernatants were measured using enzyme-linked immunosorbent assays (hIFN-γ, hIL-4, hIL-10, hIL-17 and hIL-12p70; eBioscience). 21 51 Cr release assay Cytotoxic activity was measured using the standard 51 Cr release assay, as described.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…We previously established a method to induce the proliferation of human induced pluripotent stem (iPS) cell‐derived myeloid cells to generate iPS cell‐derived myeloid/macrophage cell lines (iPS‐ML) . Similar to physiological macrophages, iPS‐ML cells expressed various receptors related to tissue infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…We previously established a method to induce the proliferation of human induced pluripotent stem (iPS) cell-derived myeloid cells to generate iPS cell-derived myeloid/macrophage cell lines (iPS-ML). [27][28][29] Similar to physiological macrophages, iPS-ML cells expressed various receptors related to tissue infiltration. When human iPS-ML cells were injected into severe combined immunodeficiency (SCID) mice bearing cancers (xenograft cancer models), iPS-ML cells accumulated and infiltrated into the cancer tissues, indicating a cancerdirected migration capacity of iPS-ML.…”
Section: Introductionmentioning
confidence: 99%